Pendampingan Pembuatan Laporan Keuangan Bagi Siswa SMK Tarbiyatut Tholabah Kranji Paciran Lamongan - Latifah, Eny; Muawanah, Rifatul; Martiwi, Wanala Abdilaila; Rohmawati, Ismy Tsaniyah Nur (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The service aims to foster creativity and motivation as well as students' soft skills in making financial reports for the needs of the world of work. The community service method used is Participatory Action Research. The results of mentoring with training show that 80% of students can quickly practice making personal and family financial reports and the rest are able to understand but have not succeeded in making them perfectly, but for training practice of making financial reports for the world of work only 50% are able to make them and The other 50% can only understand but still can't finish because it takes a longer time